A Strategy Research on MPPT Technique in Photovoltaic Power Generation System - Fu Qiang; Tong Nan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Output mode of photovoltaic cell is a complex transcendental equation, which is rather difficult to figure out by the numerical method. Traditional MPPT requests highly of initial value with low accuracy. In this thesis, simulation model of photovoltaic cell is built to simulate environmental situations under different lights and temperatures, taking advantage of particle swarm and ant colony intelligent algorithm to track the maximum power point of photovoltaic cell. Furthermore, a kind of intelligent perturbative tracking method is put forward combined with traditional perturbative tracking and intelligent tracking. The simulation result showing that intelligent perturbative tracking strategy has superior accuracy and adaptability than traditional MPPT method. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3685